La comprensión oral inglés en estudiantes del séptimo ciclo de educación básica regular en la Institución Educativa República de Venezuela de Iquitos 2023 en cuanto al sexo - Manihuari Robalino, Katia Cristina (2024)
The objective of this research study was to compare seventh cycle students’ listening skills in English at Republica de Venezuela secondary school, concerning sex, Iquitos 2023. The study type was comparative with field study, transectional contemporary, and univariate designs. It was developed with a population of 538 and a deterministic sample of 293. The material used for data collection was a listening test where the identify of each student was safeguarded by level: third, fourth, and fifth grades. Results show that male students’ mean score was slightly lower than female students’ (12.7<12,8). The same happens in its dimensions: Getting information (12.1<12,3), inferencing and interpreting (13.712.5). evaluation of content, context, and text type (12.6>12.5). The study determined that there is no statistically significant difference in English listening skills in terms of gender, as p value=0.173> α=0,05, rejecting the study hypothesis.